Haemostatic activity of butanolic extracts of Lamium album and Lamium purpureum aerial parts - Bubueanu Corina; Iuksel Rasit; Panteli Minerva (Acta Pharmaceutica)
Lamium album and Lamium purpureum are species belonging to the genus Lamium. Aerial parts of the two species and roots of Lamium album have applications in human and veterinary traditional medicine. Haemostatic properties of butanolic extracts of Lamium species were investigated by two experimental models in Wistar rats: haemostatic test by tail bleeding time determination and acenocoumarolcarrageenan test. Results of the haemostatic test by tail bleeding determination demonstrated haemostatic activity of both extracts. In the acenocoumarol-carrageenan test, only the Lamium album extract showed haemostatic activity, comparable to that of vitamin K. Based on the qualitative chemical data on iridoid glycosides (HPTLC), 8-acetylshanzhiside methyl ester might be assumed to be responsible for haemostatic activity. Based on the acute toxicity test, none of the extracts showed toxicity.